2014
DOI: 10.1097/ss.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Organic Amendments to a Wheat Crop Alter Soil Aggregation and Labile Carbon on the Loess Plateau, China

Abstract: The Loess Plateau in China is one of the most severely eroded areas in the world. Understanding the characteristics of soil aggregation and the distribution of soil organic carbon (SOC) in aggregates on the plateau is essential for improving regional soil quality. A 2-year study was conducted in a wheat cropping system on the plateau to investigate shortterm responses of soil aggregation measured via water stability and total as well as labile SOC (permanganate-oxidizable C [POXC]) fractions to organic amendme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Soil organic carbon plays a significant role in ecosystem productivity and in maintaining and improving the soil quality and nutrients. Some studies reported that the SOC content was affected by different land‐use types, crop residues, and fertilizer regime management practices (Mukumbuta, Shimizu, & Hatano, ; Wang et al., ). In this study, the SOC content decreased with increasing soil depth under the CT, RT, NT, and RTO treatments (Figure ), and similar studies also reported that the SOC content gradually decreased with increasing soil depth (0–20 cm; Lou, Xu, Chen, He, & Zhao, ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil organic carbon plays a significant role in ecosystem productivity and in maintaining and improving the soil quality and nutrients. Some studies reported that the SOC content was affected by different land‐use types, crop residues, and fertilizer regime management practices (Mukumbuta, Shimizu, & Hatano, ; Wang et al., ). In this study, the SOC content decreased with increasing soil depth under the CT, RT, NT, and RTO treatments (Figure ), and similar studies also reported that the SOC content gradually decreased with increasing soil depth (0–20 cm; Lou, Xu, Chen, He, & Zhao, ).…”
Section: Discussionmentioning
confidence: 99%